Pengaruh Pelatihan dan Upah terhadap Motivasi Kerja Pegawai PUPR Kota Binjai Sumatera Utara - Imam Azhari Ritonga; Amirudin Amirudin; Khamo Waruwu (Universitas 45 Surabaya, 2025)
The aim of this research is to determine the influence of training and wages on the work motivation of PUPR employees in Binjai City, North Sumatra. This research was carried out at the Binjai City PUPR Office with a population and sample of 42 employees. This research instrument is a questionnaire with a Likert scale model. Requirement tests were carried out to test normality, multicollinearity, heteroscedasticity tests. The data analysis technique used was the Multiple Regression technique at a significance level of a = 0.05. The results of this research show that training has a positive and significant influence on work motivation where tcount is greater than ttable with a significant value lower than 0.05. Meanwhile, wages also have a positive and significant influence on work motivation with a tcount value greater than ttable with a significant value smaller than 0.05. Based on the SPSS output, it is known that the R squared value contributes an influence of 28.7%, meaning that the variance in the work motivation variable can be explained by the training and wage variables, while the remainder is explained by other variables which are not analyzed in this model. This means that there are still other independent variables that influence work motivation.